QM-HiFSA-Aided Structure Determination of Succinilenes A–D, New Triene Polyols from a Marine-Derived Streptomyces sp. - Munhyung Bae; So Hyun Park; Yun Kwon; Sang Kook Lee; Jongheon Shin; Joo-Won Nam; Dong-Chan Oh (Marine Drugs, 2017)
Based on profiles of secondary metabolites produced by marine bacteria obtained using LC/MS, succinilenes A–D (1–4), new triene polyols, were discovered from a culture of a Streptomyces strain SAK1, which was collected in the southern area of Jeju Island, Republic of Korea. The gross structures of 1–4 were primarily determined through analysis of NMR spectra. The double bond geometries of the succinilenes, which could not be established from conventional 1H NMR spectra because of the highly overlapped olefinic signals, were successfully deciphered using the recently developed quantum-mechanics-driven 1H iterative full spin analysis (QM-HiFSA). Succinilenes A–C (1–3) displayed inhibitory effects against lipopolysaccharide (LPS)-induced nitric oxide (NO) production, indicating their anti-inflammatory significance. These three compounds (1–3) commonly bear a succinic acid moiety, although succinilene D (4), which did not inhibit NO production, does not have this moiety in its structure. The absolute configurations of succinilenes A–D (1–4) were established through J-based configuration analysis, the modified Mosher’s method following methanolysis, and CD spectral analysis.